Crystal structure of catena-poly[tribenzyl-κ1C-(μ2-6-oxidopyridin-1-ium-3-carboxylato-κ2O:O’)tin(IV)-dichloromethane-methanol (1/1/1), C29H31Cl2NO4Sn - Gao Zhongjun; Zhang Haifeng (Zeitschrift für Kristallographie - New Crystal Structures)
C29H31Cl2NO4Sn, monoclinic, P21/n (no. 14), a = 10.638(4) Å, b = 17.168(7) Å, c = 18.399(5) Å, β = 120.573(16)°, V = 2893.1(18) Å3, Z = 4, Rgt(F) = 0.0314, wRref(F2) = 0.0875, T = 298 K.